The feasibility of using solar powered submersible pumps in the State of Kuwait: جَدوى استخدام المَضَخات الغَاطسة العاملة بِالطَاقة الشمْسِية بِدولة الكويت - Abdularhman Musaed Abdulrahman Albannai, (Journal of engineering sciences and information technology, 2020)
The research aims to study the extent of the possible benefit from the solar fall falling in the state of Kuwait to operate submersible type pumps and to show the rate of flow of these pumps according to the change of solar radiation taking into account the spatial and temporal factor. The abundance of the area in southern Kuwait was chosen because there is good brightness for this area underground at different depths. As for the temporal factor, the timing of the transition was chosen between two important seasons that start from mid-January to mid-March, which is the period during which the brightness of the sun moves from the intermediate stage to the full brightness stage. The experimental study showed that the pump passes through two stages, the first of which is not operating and responding For the process of drawing if the solar radiation falling on the panels is less than 225 W/ m2, and the second stage occurs a response and operation of the pump gradually if the falling solar radiation is higher than the previous value, as the study showed that there is a large amount of external energy that is not exploited at some times of the day, especially in Sunny days, where the proportions decreased from 4.8 l/ 1000 watt to 1.5 l/ 1000 watt with an increase in the amount of energy from 430 w/ m 2 to 1005 w T/ m 2 The amount of flow fluctuated during the days of the study due to the differences in the sun's brightness and climate change, and the study was conducted using a method of taking periodic, daily and instant measurements, to determine the amount of energy and flow by using a solar radiation measuring device with a storage memory, which is a device for one of the companies that install solar energy panels And easily traded and other devices such as digital voltmeter and clip meter and water meter, the study concluded that the use of submersible pumps powered by solar energy with the presence of special characteristics such as the pump capacity, water depth and degree of brightness.